2020
DOI: 10.1093/eurheartj/suaa086
|View full text |Cite
|
Sign up to set email alerts
|

May Measurement Month 2018: an analysis of blood pressure screening results from Bangladesh

Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. According to Non-communicable disease (NCD) Risk Factors Survey Bangladesh 2010, one-fifth (21.9%) of adults aged 25 years or more have hypertension. Almost one-third of the adult population did not have their BP measured in their lifetime in Bangladesh. National Heart Foundation of Bangladesh participated in May Measurement Month (MMM) 2018 as a part of a global initiative aimed at raising awareness of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The previous three MMM campaigns showed wide variations in the percentage of hypertensive individuals and percentage of uncontrolled BP among the individuals receiving anti-hypertensive medication. In the MMM17, 47.3% were hypertensive and 52.2% uncontrolled 8 ; in the MMM18, 33.6% and 33.6% 9 ; and in the MMM19, 28.0% and 35.8%, 10 respectively. The MMM21 is the largest BP screening campaign in Bangladesh, and among the participants with hypertension and on antihypertensive medication, 66.8% had controlled BP ( Table 1 ).…”
Section: Discussionmentioning
confidence: 89%
“…The previous three MMM campaigns showed wide variations in the percentage of hypertensive individuals and percentage of uncontrolled BP among the individuals receiving anti-hypertensive medication. In the MMM17, 47.3% were hypertensive and 52.2% uncontrolled 8 ; in the MMM18, 33.6% and 33.6% 9 ; and in the MMM19, 28.0% and 35.8%, 10 respectively. The MMM21 is the largest BP screening campaign in Bangladesh, and among the participants with hypertension and on antihypertensive medication, 66.8% had controlled BP ( Table 1 ).…”
Section: Discussionmentioning
confidence: 89%
“…Overall, 16% of hypertensive subjects had their hypertension controlled (95% CI: 0.14–0.18). Three studies reported a control of hypertension <2% (Angola [ 27 ], Cameroon [ 41 ] and Ghana [ 49 ]), whereas two studies in Bangladesh [ 31 , 32 ], one in India [ 68 ] and two in Iran [ 78 , 80 ] found >40% of controlled hypertensive subjects. In LICs the percentage of controlled hypertension was lower than LMICs (11% vs .…”
Section: Resultsmentioning
confidence: 99%
“… 5 In MMM18, a total of 5208 individuals were screened, 33.6% had hypertension and among those who were on antihypertensive medication 33.6% had uncontrolled hypertension. 6 Differences in the proportions with hypertension and control rates in 2017 and 2018 may reflect that in MMM17 a large number of the participants were screened in community settings, whilst in MMM18 most of the participants were screened from hospital outdoor set-ups. Awareness of hypertension status among the hypertensive patients were very similar in all three MMM campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…The National Heart Foundation of Bangladesh (NHFB) has been working for the control and prevention of cardiovascular diseases and co-ordinated the conduct of the two previous May Measurement Month (MMM) events in 2017 and 2018, in collaboration with government and non-government organizations throughout the country, with technical support from the International Society of Hypertension (ISH). 5 , 6 In 2019, NHFB participated in another round of MMM aimed at raising awareness of high BP and to act as a temporary solution to the lack of regular BP screening programmes in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%